Letters of Gerald Finzi and Howard Ferguson - Finzi, Gerald, 1901-1956; Ferguson, Howard, 1908-1999 (Boydell Press, 2001)
Biographical insights into two outstanding musical personalities and commentary on the vitality of the British musical scene of the period. The letters that passed, on an almost daily basis, between the composers Howard Ferguson and Gerald Finzi provide not only a fascinating commentary on the British musical scene of the period 1926-1956, but also what amounts to a unique dual-biography of two remarkable, though very different, personalities. Their lives, their loves, their enthusiasms and their prejudices are laid bare with a rare degree of candour, so that we learn not only what it was liketo be witness to an art that was enjoying an unprecedented explosion of creative vitality, but also how they came to explore and consolidate their own exceptional talents. Biographical background narratives provide links that make clear what intimate correspondents inevitably take for granted, and explanations are given for references that the passage of time has made obscure. Their lives are thus revealed in all their diversity - tragedy and comedy, achievement and frustration, justifiable pride and unreasoning prejudice playing equal parts in this absorbing tale of two outstanding musical personalities of the twentieth century.